Ghosts, Vampires, Zombies, and Us: The Undead as Autoethnographic Bridges. Issue 3 (November 2014) - Herrmann, Andrew F.
In this exploration, I examine how autoethnographers create connections and community through the metaphor of the undead in their various forms. Autoethnography allows us to write and speak about our anxieties, our impolite private issues, and what frightens us at home and at work, including aging, guilt, mortality, shame, and lost love. Through autoethnography, we connect the seen and the invisible, the known and the unknown, the understood and the unexplained, mystery and science. It provides us the opportunity to reenchant the world. Most importantly, autoethnographic writing provides us the opportunity to recognize that our fears are not ours alone but are a basis upon which we can all connect.